2019
DOI: 10.31235/osf.io/djh4x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring menstrual hygiene experience: Development and validation of the Menstrual Practice Needs Scale (MPNS-36)

Abstract: Objectives. This study describes the development and validation the Menstrual Practice Needs Scale (MPNS-36) which measures the extent to which females’ menstrual practices and environments meet their needs. Methods. A 54-item pool was developed following systematic-review of qualitative and quantitative studies and expert feedback. Item reduction and scale validation were undertaken using a cross-sectional survey of 538 menstruating schoolgirls in Soroti, Uganda. Test-retest reliability was assessed in a sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
(39 reference statements)
2
22
0
Order By: Relevance
“…The derived menstrual symptoms variable showed that only 22.6% and 30.0% among respondents in public and private school respectively had a positive attitude while others showed a negative attitude, as in previous studies (42)(43)(44). The signs and symptoms that herald menarche, and subsequent menstruations on monthly basis vary from one adolescent to another, as also in the postmenarche female adolescents where a signi cant negative correlation between menstrual attitudes and perimenstrual symptoms in Uganda (45), a product of inadequate and skewed awareness, and preparedness to manage some menstruation and associated discomforts (19,32,42).…”
Section: The Attitude Of In-school Adolescent Girls To Menstruationsupporting
confidence: 61%
See 1 more Smart Citation
“…The derived menstrual symptoms variable showed that only 22.6% and 30.0% among respondents in public and private school respectively had a positive attitude while others showed a negative attitude, as in previous studies (42)(43)(44). The signs and symptoms that herald menarche, and subsequent menstruations on monthly basis vary from one adolescent to another, as also in the postmenarche female adolescents where a signi cant negative correlation between menstrual attitudes and perimenstrual symptoms in Uganda (45), a product of inadequate and skewed awareness, and preparedness to manage some menstruation and associated discomforts (19,32,42).…”
Section: The Attitude Of In-school Adolescent Girls To Menstruationsupporting
confidence: 61%
“…The ease with which adolescents communicate about menstruation, including but not limited to feelings about the purchase and handling menstruation materials, information seeking pattern, as part of openness, was largely negative, in congruence with ndings in Uganda, and other climes where a silent culture of secrecy, inadequacy, shame and insecurity pines menstruation and menstrual hygiene management (38,(45)(46)(47)(48). Also, on their acceptance of menarche, adolescents attending public and private schools had 28.2% and 35.6% positive rating scores respectively, a pointer to the inherent challenges experienced.…”
Section: The Attitude Of In-school Adolescent Girls To Menstruationmentioning
confidence: 89%
“…and 83% had gone without food, water, medicine or school supplies in the past year. Participants were selected systematically from Primary Levels 5 and 6, with additional recruitment in Levels 4 and 7 to achieve the final sample size which was based on the number of items tested for inclusion in the Menstrual Practice Needs Scale [13]. MPQ questions were included alongside the piloted scale items.…”
Section: Research Activity and Citationmentioning
confidence: 99%
“…Questions about sterilisation practices, including ironing fabric materials and boiling menstrual cups were added based on the audit of past measures. Finally, questions capturing use of the usual urination location during menstruation were added based on recent studies emphasising the importance of this practice and the lack of available data [13,14].…”
Section: Comprehensive Assessment Of Menstrual Practicesmentioning
confidence: 99%
See 1 more Smart Citation